Yakın ilişkilerde duygu körlüğü (aleksitimi) ve kişilerarası iletişim becerileri arasındaki ilişki - Kılınç, Beyza Nur (My University, 2024)
Duygular, başkaları ve kendimiz hakkında bilgi kaynakları olup insanların birbirine bağlı hissetmesine ilişkin kararlar alınmasına olanak sağlamaktadır. Duygular bu nedenle bireyin, sosyal ve bilişsel psikolojisiyle ilgilidir, ancak aynı zamanda bireylerin zihinsel ve fiziksel sağlığı üzerinde de etkiye sahiptirler. Bununla birlikte bazı insanlar sevgi, üzüntü, mutluluk, nefret gibi duyguları algılama, tanımlama ve açıklama konusunda yetersizdirler. Bu kişiler aynı zamanda başkalarının duygularını anlamakta ve empati kurmakta da zorluk yaşarlar ve duygusal tepki vermekte de yetersiz kalırlar. Bireylerin duygularını tanımlamakta ve ifade etmekte zorlandıkları bu durum “aleksitimi” olarak tanımlanmaktadır. Kelime kökeni itibariyle duygular için söz yokluğu olarak tanımlanan aleksitimi, literatürde sıklıkla ‘duygu körlüğü’ ve “duygu sağırlığı” şeklinde kullanılır ve tıbbi terminolojideki karşılığı ise ‘aleksitimi’dir. Aleksitimik bireyler yalnızca kendi duygularına karşı bir körlüğe sahip değildirler. Aynı zamanda ilişkide ve iletişimde bulunduğu kişilere karşı da duyguları okuyamama, algılayamama bozukluğuna sahiptirler. Bir kişilik özelliği olarak tanımlanan aleksitimi beraberinde iletişim bozukluklarını da getirmektedir. İletişim bozukluklarının nedenleri ve iletişim bozukluğu olan kişilerin sergiledikleri kişilerarası ilişiler davranışları bütüncül (holistik) bir yaklaşımla ele alınmalıdır. Örneğin; kişilerarası iletişim bozukluklarının temelinde patolojik, odyolojik ve psikolojik sebepler de olabileceği göz önünde bulundurulmalıdır. Aleksitimi, bireylerin empati kurma becerisini olumsuz etkiler, ilişkisel zorluklar ve iletişim sorunları yaşamalarını kaçınılmaz kılar. Konunun taşıdığı öneme rağmen YÖK ulusal veri tabanında yakın ilişkilerde aleksitimi düzeyi ile iletişim becerileri arasındaki ilişkinin incelendiği bir çalışmaya rastlanmamıştır. Aleksitimi kelimesi tek başına tüm alanlarda taratıldığında toplamda 488 sonuç çıkmakla birlikte çalışmaların tamamı psikoloji, hemşirelik, psikiyatri, dermatoloji, beslenme ve diyetetik, spor, diş hekimliği, adli tıp aile hekimliği genetik, nöroloji, gastroenteroloji ve halk sağlığı alanında olup, kişilerarası iletişim alan yazınında hiçbir çalışmaya rastlanmamıştır. Aleksitimi ve iletişim kavramları “tüm alanlarda” birlikte taratıldığında ise yalnızca 3 çalışmaya rastlanmış ve bu çalışmalarda hemşirelik, klinik psikoloji, psikolojik danışmanlık alanlarında yapılmış olup, kişilerarası iletişim alanında yine hiçbir çalışmaya rastlanmamıştır. Bu nedenle “Yakın İlişkilerde Duygu Körlüğü (Aleksitimi) ve Kişilerarası İletişim Becerileri Arasındaki İlişki” başlığıyla yapılan bu tez çalışmasının alana katkı sağlayacağı düşünülmektedir. Yürütülen tez çalışmasında kavramsal ve kuramsal temellerden bahsedilerek araştırmaya konu olan yakın ilişkiler, aleksitimi (duygu körlüğü) ve iletişim becerileri kavramlarının üzerinde durulmuştur. Çalışma nitel araştırma yöntemlerinden derinlemesine mülakat yöntemiyle yürütülen bir araştırma ile tamamlanmıştır. Çalışma 16 kadın katılımcı ile yürütülmüş olup, katılımcılara aleksitimi belirtileri, iletişim becerileri ve yakın ilişkiler hususunda sorular yöneltilmiştir. Görüşmelerden elde edilen veriler, bir nitel araştırma veri analiz olan MAXQDA fre edilmiştir. Araştırma sonuçları neticesinde kişilerin aleksitimik belirtiler gösteriyor olması ve iletişim becerileri arasında anlamlı bir ilişki olduğu bulgusuna ulaşılmıştır.

Emotions are sources of information about others and ourselves, allowing people to connect or feel connected and to make decisions about interpersonal relationships. So, emotions are relevant to the individuals’ social and cognitive psychology, but they also have an impact on the mental and physical health of individuals. However, some people are insufficient in perceiving, describing and understanding emotions such as love, sadness, happiness, hate, etc. These people also have difficulty of understanding and empathizing with the feelings of others, and they are incapable of emotionally responding. This situation, in which individuals have difficulty in understanding and expressing their emotions, is defined as alexithymia. When alexithymia was discovered, it was thought that the problem was only about disconnection between emotion and language. Today, it is known that alexithymia is not only related to this, and that some people are not aware of feeling. Alexithymia, due to the origin of the word is defined as ‘no words for emotions’, also often used in the literature as emotional blindness, emotional deafness, emotional color blindness and in medical terminology is alexithymia. Alexithymic people do not only have a blindness to their own emotions. At the same time, they have the disorder of not being able to read and perceive emotions towards the people with whom they are in contact and in communication. Alexithymia, which is defined as a personality trait,causes the communication problems. However, when we look the interpersonal communication literature, it is seen that interpersonal communication and communication problems are handled with a very limited perspective in the context of source, message and receiver, which includes the cause and effect to verbal and non-verbal messages. However, the causes of communication problems and the interpersonal behavior of people with communication problems should be discussed with a holistic approach. For example, it should be taken into consideration that there may be pathological, audiological and psychological causes of the interpersonal communication problems. It should be understand that it is common for an individual who has difficulties with communication to suffer damage to other areas of social life as well. Researchers say that alexithymia is a problem with a very high prevalence in the world and one out of every 10 people is alexithymic. Because in today's modern society, the individual is getting more and more lonely with each passing day, and people are sharing emotions with other people is decreasing day by day. They get a life in which they cannot find the opportunity to express their feelings due to the limited communication environment in working life. The individual, who doesnt share emotions with others, even he is in crowd he leads a lonely life. Therefore, the individual who lives life, without sharing his feelings with others, becomes blind and deaf to his own feelings as well as to others, and becomes unable to distinguish between his anger and his joy. Shortly, alexithymia negatively affects individuals' ability to empathize, having difficulties in relations and communication problems. So, effective communication with people is possible by recognizing the emotions of others and expressing and understandihg their own emotions effectively. The aim of this study is to examine the relationship between individuals' alexithymia levels and communication skills in close relationships. Because in effective communication process in close relationships, the ability of individuals to understand, express and be aware of their emotions have great importance. For this reason, it is important for individuals to understand the alexithymia levels in interpersonal relationships, to examine whether there is a relationship between alexithymia levels and communication skills, and to improve interpersonal communication skills to increase emotional awareness. Despite the importance of the subject, no study about the relationship between alexithymia level and communication skills in close relationships was found in the database of YÖK. When the word ‘alexithymia’ is scanned in all fields, a total of 269 results are found. All of the studies were in the fields of psychology, nursing, psychiatry, dermatology, nutrition and dietetics, sports, dentistry, family medicine, genetics, neurology, gastroenterology and public health, and no study was found in the interpersonal communication literature. When the concepts of ‘alexithymia and communication’ were scanned together in all fields, only 3 studies were found and these studies were conducted in the fields of nursing, clinical psychology, and psychological counseling, but no study was found in the field of interpersonal communication. In addition, no study was found when the concepts of emotional blindness, emotional deafness, and emotional color blindness. For this reason, this thesis study, which named as The Relationship Between Emotion Blindness (Alexithymia) and Interpersonal Communication Skills in Close Relationships will contribute to the field.. This study will be completed with a field research after a theoretical explanations and the literature review.
Keywords: Aleksitimi; Close Relationships; Duygu körlüğü Alexithymia; Interpersonal communication; Kişilerarası iletişim; Kişilerarası iletişim becerileri; Yakın ilişkiler